2021
DOI: 10.1111/1462-2920.15306
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved organic matter released by two marine heterotrophic bacterial strains and its bioavailability for natural prokaryotic communities

Abstract: Marine heterotrophic prokaryotes (HP) play a key role in organic matter processing in the ocean; however, the view of HP as dissolved organic matter (DOM) sources remains underexplored. In this study, we quantified and optically characterized the DOM produced by two single marine bacterial strains. We then tested the availability of these DOM sources to in situ Mediterranean Sea HP communities. Two bacterial strains were used: Photobacterium angustum (a copiotrophic gammaproteobacterium) and Sphingopyxis alask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 63 publications
3
15
0
Order By: Relevance
“…Photochemical reactions (or photo‐bleaching) solely have been demonstrated to transform DOM from refractory to a relatively labile state (Medeiros et al ., 2015, Stubbins et al ., 2010), and this abiotic reaction is restricted in the photic zone. In the deep and dark ocean interior, the molecular conformity of DOM could be majorly linked with microbial activities (Ortega‐Retuerta et al ., 2021), but the experimental evidence is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Photochemical reactions (or photo‐bleaching) solely have been demonstrated to transform DOM from refractory to a relatively labile state (Medeiros et al ., 2015, Stubbins et al ., 2010), and this abiotic reaction is restricted in the photic zone. In the deep and dark ocean interior, the molecular conformity of DOM could be majorly linked with microbial activities (Ortega‐Retuerta et al ., 2021), but the experimental evidence is limited.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study has demonstrated that Alteromonas have a limited ability to degrade DOM compared to natural microbial communities over longer terms (Pedler et al 2014). We also found a difference in DOC utilization between Alteromonas and natural microbial community, which could be due to that natural populations undergo succession which increase the niche breadths and DOM degradation (Bunse and Pinhassi 2017; Ortega‐Retuerta et al 2021). We further assessed the extent to which DOM or microbial composition is potentially responsible for this divergence.…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies have shown that axenic cultures of multiple species of algae contribute to detectable humic-like DOM in the ocean ( 21 ), while others indicated that aggregation of recalcitrant DOM results from microbial processing (mainly bacteria) of planktonic-precursors ( 22 ). Incubation experiments have also demonstrated that heterotrophic bacteria in the marine environment can convert glucose, glutamic acid, oligosaccharides, and algae extracts into highly diverse recalcitrant components ( 16 , 23 , 24 ). These exometabolites directly released by bacteria upon utilization of labile substrates ought to have intrinsic properties rendering them resistant to decomposition and therefore allowing them to remain recalcitrant for a long time ( 16 , 21 , 25 27 ).…”
Section: Introductionmentioning
confidence: 99%